2005
DOI: 10.1146/annurev.neuro.27.070203.144137
|View full text |Cite
|
Sign up to set email alerts
|

AUTISM: A Window Onto the Development of the Social and the Analytic Brain

Abstract: Although the neurobiological understanding of autism has been increasing exponentially, the diagnosis of autism spectrum conditions still rests entirely on behavioral criteria. Autism is therefore most productively approached using a combination of biological and psychological theory. The triad of behavioral abnormalities in social function, communication, and restricted and repetitive behaviors and interests can be explained psychologically by an impaired capacity for empathizing, or modeling the mental state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
182
0
11

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(201 citation statements)
references
References 133 publications
8
182
0
11
Order By: Relevance
“…Regions of the 'social brain network', including the superior temporal sulcus and the amygdala have also been found to exhibit atypical activation patterns in individuals with autism (Baron- Cohen & Belmonte, 2005;Hadjikani, et al, 2004;Pelphrey et al, 2005). Recently, in an adult sample with autism, Koshino et al (2008) found activation in a different location in the fusiform area in response to faces compared to control participants.…”
Section: Holistic Processing In Developmental Disordersmentioning
confidence: 99%
“…Regions of the 'social brain network', including the superior temporal sulcus and the amygdala have also been found to exhibit atypical activation patterns in individuals with autism (Baron- Cohen & Belmonte, 2005;Hadjikani, et al, 2004;Pelphrey et al, 2005). Recently, in an adult sample with autism, Koshino et al (2008) found activation in a different location in the fusiform area in response to faces compared to control participants.…”
Section: Holistic Processing In Developmental Disordersmentioning
confidence: 99%
“…In addition, we assessed the relation between cortical thickness in specific regions implicated in social and communication functions and symptom severity. In this latter analysis, a priori regions of interest (ROIs) included anterior cingulate cortices (ACC), medial prefrontal cortices (mPFC), orbital frontal cortices (OFC), inferior frontal gyri (IFG), the superior temporal gyri (STG) and fusiform gyri because of their involvement in social behaviours and communication (Baron-Cohen & Belmonte, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Abnormal brain functioning has been reported in autistic subjects, particularly in the cortical networks involved in social interaction, such as the medial and inferior frontal cortex, the medial and ventral temporal lobes, superior temporal sulcus, amygdala and cerebellum. 17,18 We investigated the possible deregulation of SCL25A12 expression in autism, using mRNA extracted from post-mortem tissues from autistic individuals and controls, focusing on two regions: frontal cortex BA46 and cerebellum hemisphere lobule VI granule cells.…”
Section: Introductionmentioning
confidence: 99%